Quantification of Physiochemical Characteristic Wastewater Effluents a Case Study of Bata Tanneries, Kenya - Maritim , Geoffrey K.; Kipkemboi , Pius; Lusweti , Kituyi (African Journal of Education,Science and Technology (AJEST), 2022)
The tanning industry is well developed in Kenya and has been identified as one of the most important sectors in economic development. However, depending on the leather process, it generates large quantities of wastewater with ammonium, sulphates, surfactants, acids, dyes, sulphonated oils and organic substances, heavy metals Cr, Pb and natural or synthetic tannins. Bata leather industries in Kenya have been discharging effluent to nearby rivers leading to human and environmental pollution. The current study sought to carry out quantification of physicochemical characteristics of tannery wastewater effluents: “A case study of Bata Tanneries, Kenya”. Water samples from four sampling points (S1 – Pre-tanning Stage, S2 – Tanning Stage, S3 – Post-tanning Stage and S4 – Drainage to the river) were collected using a clean grab sampler. The samples were transported in cool box to the chemistry laboratory of the Tea research foundation of Kenya for analysis. Physiochemical parameters were determined from the collected samples and results were compared with NEMA, KEBS and WHO set standards. The mean range levels obtained from (S1-S4) Bata leather tanneries in Kenya were as follows; total dissolved solids (TDS) 137.7 and 270 mg/L, DO 8.4 and 10.6 mg/L, pH concentrations ranged between 1.52 and 8.2. EC 1348.8 and 1385 mS/cm at S3, temperature 22.7 and 27.9 o, biological oxygen demand (BOD) 3141.2 and 5477.7 mg/L, total suspended solids (TSS) 148 mg/l to 284 mg/L, total solids (TS) 286 and 554 mg/L. Chemical oxygen demand (COD) 5986.7 to 9093.2 mg/L, colour (Pt-Co) 488.5 and 787.2 Pt-Co. All values of physicochemical parameters exceeded KEBS, NEMA and WHO standards except for temperature which was within the range. The ministry of Environment should enforce the law concerning water pollution and prosecute those who are found culpable. Polluter pay principle should be applied to the company.